Measuring Logbook Usage to Support Work From Home During Covid-19 Pandemic Using Technology Acceptance Model - Yusuf, Muhammad; Prasasti, Rimba; Muktianto, Ageng (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
After Coronavirus have first detected in Indonesia, the Government issued a Large-Scale Social Restriction (PSBB) policy to reduce its spread. One of the PSBB policies is working from home (WFH). Directorate General of Taxes builds a Logbook to monitor employee activities such as reporting work, employee health, attendance, and location detection. This study measures the use of Logbooks to support WFH during the Covid-19 pandemic using an extension of the Technology Acceptance Model (TAM) by adding the variables of habit, perceived risk, performance measurement, and trust. Hypothesis testing using reliability test, validity test, Kolmogorov Smirnov test, t-test, and SEM test. Results of the research obtained that logbook could be accepted by employees to support WFH during the Covid-19 pandemic.